2011
DOI: 10.1091/mbc.e11-01-0048
|View full text |Cite
|
Sign up to set email alerts
|

Role for casein kinase 1 in the phosphorylation of Claspin on critical residues necessary for the activation of Chk1

Abstract: Claspin mediates the activation of checkpoint kinase 1 (Chk1) by ATM- and Rad3-related kinase (ATR) in response to genomic stress. This process depends upon phosphorylation of Claspin on two critical residues. These phosphorylations allow docking of Claspin with Chk1. In this study, we identified CK1γ1 as a kinase that carries out these key phosphorylations of Claspin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…It has been reported that CK1g1 plays an important role in activating the ATR/Chk1 pathway by phosphorylating Claspin, which was identified as a Chk1-activating protein (23). In this study, we found that CK1g1 can phosphorylate NF-kB subunit p65 at Ser 536 , which promotes its ubiquitin-mediated degredation by E3 ligases COMMD1 and CUL2.…”
Section: Discussionmentioning
confidence: 53%
“…It has been reported that CK1g1 plays an important role in activating the ATR/Chk1 pathway by phosphorylating Claspin, which was identified as a Chk1-activating protein (23). In this study, we found that CK1g1 can phosphorylate NF-kB subunit p65 at Ser 536 , which promotes its ubiquitin-mediated degredation by E3 ligases COMMD1 and CUL2.…”
Section: Discussionmentioning
confidence: 53%
“…15), and CDC7 (16,17). Phosphorylation of CLASPIN at its N-terminus by PLK1 can also contribute to switching off CHK1 once the damage is repaired, thus allowing cells to progress in the cell cycle (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Although the ATR-Chk1 kinase cascade is clearly the backbone of the ATR signaling pathway, several other protein kinases, such as ATM (6,7), CDKs (cyclin-dependent kinases) (8)(9)(10), PLK1 (polo-like kinase) (11)(12)(13)(14), AKT (15,16), and casein kinases (17,18), have been implicated in tuning the strength and dynamics of ATR signaling in different contexts. The effects of these kinases on ATR signaling suggest that the ATR pathway is intertwined with other signaling pathways and cellular programs.…”
mentioning
confidence: 99%